Drug interaction detection and glycemic control - telepharmacy's role in diabetes management: before-after study - Ida Lisni; Irma Rahayu Latarissa; Lucia Rizka Andalusia; Keri Lestari (Pensoft Publishers, 2024)
Introduction: Diabetes management faces intertwined challenges like polypharmacy and adherence complexities, hindering effective care delivery. Telepharmacy emerges as a promising solution, revolutionizing diabetes care by enhancing pharmacists' pivotal role. However, a tailored model for Indonesia is still lacking. Purpose: This study aimed to assess the potential effectiveness of a telepharmacy application in improving the detection of drug-drug interactions and glycemic control. Methods: We conducted an observational before-and-after study among type 2 diabetic patients in Indonesia. Results: We noted a significant surge in detected drug interactions. Patients counseled through telepharmacy had 3.653 times higher likelihood of achieving good glycemic control. Conclusion: The study underscores the positive impact of telepharmacy on drug interaction detection and glycemic control among Indonesian diabetics.